Les marqueurs de l’argumentation : constante ou variable ? - Stefan Goltzberg (Corela)
This papers shows that the meaning of transitional keywords is stable and hardly depends on the context. I focus on the following counter-oriented keywords: in French, “bien que”; in English, “however”; in Hebrew, “af al pi she”. I meet the objections according to which their meaning varies depending on the context. The consequences of my claim are far-reaching since it would mean that in the case of a problematic sentence (contradictory, trivial or unintelligible) containing such a keyword, one should consider reading another meaning in the other word classes and only then in the keywords.